Joint Associations of Moderate-To-Vigorous Physical Activity and Sedentary Time with Adiposity and Cardiometabolic Risk Factors in Adolescents - Suarez-Reyes, M (Lippincott Williams and Wilkins, 2025)
Purpose This study aims to explore the joint associations of moderate-to-vigorous physical activity (MVPA) and sedentary time (ST) with adiposity and cardiometabolic risk factors in adolescents. Methods A cross-sectional study was conducted on 309 participants (10-16 yr old). Measurements included accelerometer-measured MVPA and ST, anthropometrics, body composition, and cardiometabolic risk factors. MVPA and ST were categorized as high or low based on median values (MVPA 27.7 min·d-1, ST 597.7 min·d-1). General linear models assessed associations of MVPA and ST with adiposity and cardiometabolic risk factors, adjusted for covariates. Results We observed significant inverse associations between MVPA and adiposity measures. Thus, participants in the low MVPA category, compared with those in the high category, had higher body mass index (BMI; 2.23 units), z-BMI (0.43 units), waist circumference (6.1 cm), fat mass (4.6 kg), body fat (3.9%), and visceral fat (0.13 L), indicating that higher MVPA is linked to healthier body composition. No significant associations were found between ST and adiposity. MVPA was also negatively associated with some cardiometabolic risk factors, whereas ST showed no significant associations. Conclusions This study highlights the need to prioritize increasing MVPA among adolescents to support healthy body composition and improve cardiometabolic health. Although ST did not show significant associations, it remains important to limit sedentary behaviors due to their potential contribution to negative health outcomes later in life. © 2025 by the American College of Sports Medicine.